Team Performance in Flood Emergency Response: A Conceptual Model and Scale Development - lateef Saeed, Naglaa Abdel; Zakaria, Nor Hidayati; Sutoyo, Edi (International Journal of Integrated Engineering, 2018)
Based on the literature on knowledge integration, social media, and emergency management, the purpose of this paper to present our conceptual model of EM team performance and propose a rigorous approach in scale development and validation it, scale which can be used to assess organizations volunteer and staff work on flood field used social media. This study conceptualizes the construct of EM team performance and generates an initial 39 item EM task scale. Based on the sample data, this study provides an empirical validation of the EMTP constructs and its underlying dimensionality, and develops a generic EMT scale with desirable psychometric properties, including face validity, content validity and pilot testing. This study develops and validates a 30-item EM task scale with 6 constructs (task characteristic, task technology, task technology fit, social media usage, knowledge integration and EM team performance). This study is a pioneering effort to develop and validate EMTP scale and will contribute to the development of knowledge integration literature and add to the repository of rigorous research instruments for researcher’s utilization.